Elimination of visceral leishmaniasis on the Indian Subcontinent: critical knowledge gaps to be answered to get us there - Singh, Om Prakash (Lancet Infect Dis, 2016)
Visceral leishmaniasis (VL) is a serious public health problem on the Indian subcontinent, causing high morbidity and mortality. The governments in the region have launched a VL elimination initiative since 2005. We review current knowledge gaps and Research priorities. Key challenges include low health services coverage of those most at risk, drug resistance, the lack of a vaccine and the complex biology of the sand fly-human host transmission cycle. Vector control is an essential component, but innovation in this field is critically lacking. Significant progress has been made in the area of diagnostic, therapeutic and vaccine development, but there are still many hurdles to overcome. For VL elimination to become a reality, effective deployment of these existing and new tools is essential. A strong commitment at community level is imperative, and appropriate diagnostic and treatment services as well as effective epidemiological surveillance need to be ensured.